Biology of Incidental Catch Sea Star Stellaster childreni Gray, 1840 (Echinodermata: Asteroidea), from Malaysian Borneo Exclusive Economic Zone - Ruhana, Hassan; Suet, Yee Lee; Wan Zabidii, Wan Morni (Hindawi Publishing, 2017)
Sea star (class Asteroidea, phylum Echinodermata) is one of the most successful marine organisms inhabiting a wide range of habitats. As one of the key stone species, sea stars are responsible for maintaining much of the local diversity of species within certain communities.Malaysian Exclusive Economic Zone (EEZ) Resource Survey had been carried out from 16th Aug to 6th Nov 2015 and one of the invertebrate by-catch organisms is sea star Stellaster childreni Gray, 1840. This study documents morphological characters and diet of the sea star, besides providing brief descriptions of the habitats based on particle size analysis and vessel log data sheet. A total of 217 individuals had been examined throughout this study. Fragments of flora and fauna were found in the gut includingMollusca (gastropod, bivalves, and scaphopods), sponge seagrass, and seaweed as well as benthic Foraminifera. Stellaster childreni were found at depth of 45m to 185m in the South China Sea off Sarawak Malaysia, with various sea bottom substrata. Approximately 41% of S. childreni were found at a mixture of sandy andmuddy substratum, followed by mixture of sandy and coral (19.3%), muddy substratum (17.5%), coral substratum (11.5%), and sandy areas (10.6%).The widely distributed sea star on different types of sea beds suggested healthy deep sea ecosystem; thus Malaysia should explore further potential fisheries resources in the EEZ off Sarawak coast.